Quality of milk fat obtained from cows and buffaloes fed a diet supplemented with flaxseed or soybean oils - Shazly, Ahmed Behdal; Hassan, Laila Khaled; Kholif, Abd El-Kader Mahmoud; Sayed , Ahmed Farouk; Abd El-Aziz, Mahmoud (Acta Scientiarum. Animal Sciences, 2022)
The experiment was carried out to evaluate the quality of anhydrous milk fat (AMF) of cows and buffaloes supplemented with flaxseed oil (FO), soybean oil (SO), or their mixture (FSO). Lactating crossbred cows and buffaloes were fed with control diet or with one of three supplements: 2% FO, 2% SO, and 2% FSO according to a double 4 x 4 Latin Square Design. The diets with FO, SO, or FSO reduced saturated FA, mainly C4:0, C14:0 and C16:0, while increased the unsaturated FA C18:1 and C18:2 in milk from cows and buffaloes. Cholesterol content decreased in cow’s AMF while increased in buffalo’s AMF when a diet supplemented with FO, SO, or FSO. The diet with SO or FSO increased the content of vitamin E in AMF obtained from cows (25.06 and 17.89 mg 100 g-1) and buffaloes (28.48 and 30.32 mg 100 g-1) compared with the control diet (11.02 and 15.68 mg 100 g-1), respectively, which correlated positively with scavenging activity for DPPH• (r2 = 0.66) and ABTS• (r2 = 0.67) radicals. Solid fat content (SFC) was high for cow’s AMF, with 58.12-60.37% at 5°C compared to that of buffalo’s AMF, with 52.37-56.98%, but was low for cow’s AMF at >15°C. Finally, supplementing a diet with vegetable oils, particularly SO, improves the quality of AMF; increases USFA/SFA ratio, vitamin E content, and antioxidant activities